12‐2: 3D Pixel Configurations for Optical Out‐Coupling of OLED Displays — Part II: Experimental Validation. Issue 1 (29th May 2019) - Chen, Chung-Chia; Lin, Wan-Yu; Xu, Lisong; Yu, Gang; Kwak, B. Leo; Visser, Robert Jan; Chen, Yi-Ting; Wen, Sheng-Wen; Lee, Wei-Kai; Liao, Po-Hsiang; Lee, Min-Chia; Chen, Yi-Jiun; et al.
Abstract : The light extraction efficiency of OLED is crucial for display performance and other issues such as power consumption, lifetime, and image sticking issue. Although lots of effort was adopted, the existing technologies are either too difficult/expensive to be utilized or only suitable for bottom‐emitting OLEDs. Here we proposed a novel 3D pixel configuration to have effective light out‐coupling for top‐emitting OLEDs. Comprehensive multi‐scale optical simulation indicates several‐fold of extraction enhancement and excellent viewing characteristics are simultaneously achievable by extending the bottom reflective electrode to bank slope of the pixel definition layer (PDL) and selectively filling the bank opening (concave area) with high‐index filler to form the optically reflective concave structure. This scheme is scalable and wavelength insensitive, and thus can be generally applied to all red, green, and blue pixel OLEDs in high‐resolution full‐color displays. In this paper, the experiment results of validation were reported with discussion.